Comparison of a low Hartmann's procedure with low colorectal anastomosis with and without defunctioning ileostomy after radiotherapy for rectal cancer: results from a national registry. (2nd August 2016) - Jonker, F. H. W.; Tanis, P. J.; Coene, P. P. L. O.; Gietelink, L.; van der Harst, E.; ,
Abstract: Aim: This study used a national registry to compare the outcome after a low Hartmann's procedure (LHP), defined as removal of most of the rectum to leave a short anorectal stump and an end colostomy, and low anterior resection (LA) with or without a diverting ileostomy (DI) in rectal cancer patients all of whom had received preoperative neoadjuvant radiotherapy (RT). Method: Patients who underwent LHP or LA with or without DI for rectal cancer after RT between 2009 and 2013 were identified from the Dutch Surgical Colorectal Audit. The postoperative outcome was compared between the three groups and risk of complications, reoperation and mortality were analysed in a multivariable model. Results: The study included 4288 patients were included, of whom 27.8% underwent LHP, 20.2% LA and 52.0% LA with DI. Thirty‐day mortality was higher after LHP (3.2% vs 1.3% and 1.3% for LA with or without DI, P  <   0.001), but LHP was not an independent predictor of mortality in multivariable analysis. LHP and LA with DI were associated with a lower rate of abdominal infective complications (6.5% and 10.1% vs 16.2%, P  <   0.001) and reoperation (7.3% and 8.1% vs 16.5%, P  <   0.001). In multivariable analysis, LHP (OR 0.35, 95% CI 0.26–0.47) and LA with DI (OR 0.43, 95% CI 0.33–0.54) were associated with a lower risk of reoperation than LA alone. LHP was associated with a lower risk of any postoperative complication than LA with or without DI (OR 0.81, 95% CI 0.66–0.98). Conclusion: LHP and LA with DI were associated with fewer infective complications and reoperations than LA alone. The rate of any complication was less after LHR than LA with or without DI.